SHM of a masonry chimney after a lightning accident - Ramos, Luís F. (2013)
The paper focuses on the SHM works carried out on a historical masonry chimney located in a former industrial complex in Guimarães city centre, Portugal. The chimney was hit by a lightning in the morning of July 26th, 2012. The electrical discharge blew the chimney wall creating two significant openings. After the accident, an intervention was planned and executed to reestablish its sound structural condition. Before and during the structural works, a SHM plan was put into practice. Several ND tests were performed aiming at evaluating the loss of stiffness and mass, as well to control the execution of the rehabilitation works. A permanent dynamic identification system was installed in the chimney and the evolution of modal properties was followed during the site works. A FE model was built and calibrated with inverse problems to the two structural conditions. Finally, all the information was merged to evaluate the effectiveness of the rehabilitations works. The paper presents detailed information about the damage, the two structural conditions before and after the intervention works and the SHM results.